Exponential stabilisation of nonlinear parameter-varying systems with applications to conversion flight control of a tilt rotor aircraft. Issue 11 (2nd November 2019) - Fu, Rong; Sun, Hongfei; Zeng, Jianping
ABSTRACT: The exponential stabilisation problem of nonlinear parameter-varying (NPV) systems with input constraints is investigated. Unlike the existing NPV-related works, this paper directly addresses NPV models to conduct the stabilisation problem, without hiding nonlinearities or ignoring the time-varying nature. Existence conditions of a nonlinear time-varying (NTV) controller to render the uniformly exponential stability of an NPV system are given in terms of state-and-parameter-dependent linear matrix inequalities (SPLMIs). Specifically, a new controller structure and a novel Lyapunov functional are adopted such that the exact variation rates of the state and parameters can be incorporated into the SPLMIs. The generalised S-procedure is used to convexify the input constraints such that the resulting closed-loop system satisfies input constraints for any state starting from an admissible set. The derived SPLMIs can then be efficiently solved via sum-of-squares programming. The proposed approach is applied to the conversion flight control of a tilt rotor aircraft.